Fourier-Transform InfraRed Spectroscopy Can Quickly Type Gram-Negative Bacilli Responsible for Hospital Outbreaks - Martak, Daniel; Valot, Benoît; Sauget, Marlène; Cholley, Pascal; Thouverez, Michelle; Bertrand, Xavier; Hocquet, Didier (Frontiers in Microbiology, 2019)
The typing of epidemic bacterial pathogens in hospitals relies on DNA-based, expensive, and time-consuming techniques, that are often limited to retrospective studies. However, the quick identification of epidemic pathogens in the routine of the microbiology laboratories would expedite infection control procedures that limit the contamination of new patients. IR Biotyper (Bruker Daltonics GmbH) is a new typing machine based on Fourier-transform infrared (FTIR) spectroscopy, aiming at typing the micro-organisms within 3 hours based on the difference in polysaccharides spectra. In this work, we evaluated the ability of the FTIR spectroscopy to recognize Gram-negative bacilli clones responsible for hospital outbreaks. Isolates of Pseudomonas aeruginosa (n = 100), Klebsiella pneumoniae (n = 16), Enterobacter cloacae (n = 23), and Acinetobacter baumannii (n = 20) were typed by the reference methods Multi-Locus Sequence Typing (defining sequence types – STs) along with or without pulsed field gel electrophoresis (PFGE) (defining pulsotypes), and by FTIR spectroscopy. The congruence of FTIR spectroscopy clustering was compared to those of MLST and PFGE by Adjusted Rand index and Adjusted Wallace coefficient. We found that FTIR spectroscopy accurately clustered P. aeruginosa, K. pneumoniae, and E. cloacae isolates belonging to the same ST. The performance of the FTIR spectroscopy was slightly lower for A. baumannii. Furthermore, FTIR spectroscopy also correctly clustered P. aeruginosa isolates having a similar pulsotype. Overall, the IR Biotyper can quickly (in less than 3 hours) detect the spread of clones of P. aeruginosa, K. pneumoniae, E. cloacae, and A. baumannii. The use of this technique by clinical microbiology laboratories may help to tackle the spread of epidemic clones by the quick implementation of infection control measures.